2020
DOI: 10.3390/su12073060
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Concept in the Context of Economic Development in EU Countries

Abstract: The need has arisen to implement a circular economic model that enables economic growth and prosperity in accordance with environmental protection and sustainable development because of the current unsustainable linear means of production in the economy. The aim of this paper is to determine the application of the circular economy concept in member countries of the European Union from 2008 to 2016. The purpose is to analyse whether economic development measured by GDP (gross domestic product) affects the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 53 publications
1
46
0
1
Order By: Relevance
“…As a result, all new cars registered as of 2035 will be zero-emission [23]. Considering that the average age of vehicles in EU is 11.5 years, the end-of-life vehicle recycling policies become very important [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, all new cars registered as of 2035 will be zero-emission [23]. Considering that the average age of vehicles in EU is 11.5 years, the end-of-life vehicle recycling policies become very important [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Sverko Grdic et al [11], based on an econometric model, showed that applying the concept of a circular economy can provide economic growth and GDP growth while reducing natural resources and ensuring more excellent environmental protection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pertumbuhan ekonomi yang berprinsip pada ketahanan lingkungan dapat memberikan kontribusi pada aspek investasi dan dinamisme yang diperlukan untuk menyebarkan dan mengembangkan teknologi baru, yang merupakan dasar untuk mengelola aset lingkungan dan pertumbuhan produktivitas (Busu and Trica, 2019). Penerapan konsep ekonomi sirkular dengan pendekatan variabel timbunan sampah Kota per kapita, tingkat daur ulang sampah Kota, tingkat daur ulang limbah kemasan menurut jenis kemasan, tingkat daur ulang limbah organik, dan tingkat daur ulang limbah elektronik dapat meningkatkan pertumbuhan ekonomi berkualitas keberlanjutan dan pertumbuhan PDB secara inklusif sekaligus mengurangi penggunaan sumber daya alam dan memastikan perlindungan lingkungan yang lebih besar (Grdic, Nizic and Rudan, 2020).…”
Section: Pendahuluanunclassified